KONSEP PENDIDIKAN MULTIKULTURAL DALAM PRAKTIK PENDIDIKAN DI INDONESIA DAN AMERIKA - Fikri Muhammad Latif; Acep Rahmat Acep Rahmat; Nindi Ikli Kamila; Ahmad Faishal Sopyan (Yayasan Al-Afif, 2024)
This article discusses the implementation of multicultural education in Indonesia and the United States, taking into account the different historical, social, and political contexts in the two countries. Indonesia is a country rich in ethnic, cultural and religious diversity, which becomes social capital and requires inclusive and pluralist education to maintain social cohesion in the midst of plurality. On the other hand, multicultural education in the United States emerged as a response to the civil rights struggle and efforts to accommodate diversity amid the dominance of the white majority group. The implementation of multicultural education in America focuses on cultivating identity through an inclusive curriculum, while in Indonesia, multicultural education is more directed at building harmonization and tolerance between ethnic groups in order to maintain national unity. This research uses a qualitative approach with a literature study, collecting data from various literature sources. The findings show that although the general goal of multicultural education in both countries is similar, namely to build a just and democratic society, the way it is implemented is strongly influenced by the context of each country. In the United States, the implementation of multicultural education is driven by the principles of equal rights and social justice, while in Indonesia it emphasizes the formation of a pluralist and tolerant national character. This research provides insights into multicultural education approaches that can be learned and applied according to the social and cultural characteristics of each country.